Psychological factors and future performance of football players: A systematic review with meta-analysis - Ivarsson, A.; Kilhage-Persson, A.; Martindale, R.; Priestley, D.; Huijgen, B.; Ardern, C.; McCall, A. (Journal of Science and Medicine in Sport, 2020)
Objectives: This systematic review had 3 key objectives: (1) to investigate whether psychological factors were associated with future football performance (e.g., progression to professional football, better game statistics during the next season); (2) to critically review the methodological approaches used in the included studies and summarize the evidence for the current research question; (3) to provide guidelines for future studies. Design: Systematic review. Methods: Electronic databases (SPORTDiscus, PubMed and PsycINFO) and previously published systematic and scoping reviews were searched. Only prospective studies were considered for inclusion. Results: Eleven published studies that reported 39 effect sizes were included. Psychological factors; task orientation, task-oriented coping strategies and perceptual-cognitive functions had small effects on future performance in football (ds = 0.20-0.29). Due to high risk of bias there were low certainty of evidence for psychological factors relationship with future football performance. Conclusions: Psychological factors investigated showed small effects on future football performance, however, there was overall uncertainty in this evidence due to various sources of bias in the included studies. Therefore psychological factors cannot be used as a sole deciding factor in player recruitment, retention, release strategies, however it would appear appropriate to include these in the overall decision-making process. Future, studies with more appropriate and robust research designs are urgently needed to provide more certainty around their actual role.